2019
DOI: 10.12681/mms.19314
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of functional diversity of macroinvertebrates across three aquatic ecosystem types, NE Mediterranean

Abstract: This study is focused on investigating the variation patterns of macroinvertebrate guilds functional structure, in relation to the taxonomic one, across aquatic ecosystem types along the salinity gradient from freshwater to marine and the resulting implications on guild organization and energy flows. Synoptic samplings have been carried out using the leaf-pack technique at 30 sites of the aquatic ecosystems of the Corfu Island (Greece), including freshwater, lagoon, and marine sites. Here, we analyzed the macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
(85 reference statements)
1
6
1
Order By: Relevance
“…The patterns of the LSDR across the two floodplain channels, considering the whole dataset including all the months, were both statistically significant, with similar slopes (i.e., −0.39 and −0.33 for MOLO and PONT, respectively) that were significantly shallower than predicted by Damuth [8][9][10]. Our patterns were consistent with several studies that suggested that the relationship between body size and abundance is much shallower than the value of −0.75 for aquatic macroinvertebrate communities (e.g., [26,[50][51][52]) and other animal communities (e.g., [19,[53][54][55][56]). However, the shallower slopes found were not consistent with the EER.…”
Section: Patterns Of Lsdr Molo and Lsdr Pont (All Months Included)supporting
confidence: 89%
“…The patterns of the LSDR across the two floodplain channels, considering the whole dataset including all the months, were both statistically significant, with similar slopes (i.e., −0.39 and −0.33 for MOLO and PONT, respectively) that were significantly shallower than predicted by Damuth [8][9][10]. Our patterns were consistent with several studies that suggested that the relationship between body size and abundance is much shallower than the value of −0.75 for aquatic macroinvertebrate communities (e.g., [26,[50][51][52]) and other animal communities (e.g., [19,[53][54][55][56]). However, the shallower slopes found were not consistent with the EER.…”
Section: Patterns Of Lsdr Molo and Lsdr Pont (All Months Included)supporting
confidence: 89%
“…Table 5. Results of the LSR analyses of log10 population density (number of individuals per m 2 ) in relation to log10 body size (AFDW: ash free dry weight) of macroinvertebrate communities in Mediterranean and Black Sea lagoons (data from [29,30]). Table 6.…”
Section: Across Trophic Levelsmentioning
confidence: 99%
“…The energy available to them from abundant, easily acquired detritus and fine organic matter in the water column and at the bottom of lagoons is much more abundant than that available to predators that feed chiefly on animal tissue, which is more difficult A B Figure 3. Scaling of population density versus body size (AFDW: ash free dry weight) across macroinvertebrate communities in Mediterranean and Black Sea lagoons (data from [29,30]): A) CCSR for all assemblages at various sampling sites; (B) CCSRs for prey and predators analyzed separately across sampling sites. Note that since the mean body size and population density were analyzed separately for prey and predator species across sampling sites, the number of points are greater and located at different positions in graph (A) vs. graph (B).…”
Section: Across Trophic Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These communities are proved to be different in many respects. • The patterns of macroinvertebrate guild functional structure, in relation to the taxonomic one, across salinity gradients, and their implications on guild organization and energy flows in the aquatic habitats of the North-Eastern Mediterranean Sea in Greece, Corfu Island, Greece, are discussed by Gjoni et al (2019).…”
mentioning
confidence: 99%